Kualitas Tidur Remaja di Kota Palangka Raya - Maria Magdalena Purba; Icha Seveny Febriana; Ester Inung Sylvia (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2023)
Abstract : Sleep quality is the individual's ability to stay asleep, not just the amount or duration of sleep. Sleep quality shows the individual's ability to sleep and get the amount of rest that suits his needs. The quality of a person's sleep can be influenced by environmental, physical, activity, and lifestyle conditions. This study aims to determine the factors that can affect the quality of sleep in adolescents in the city of Palangka Raya. Methods Cross-sectional research with a cross sectional design. The number of samples was 98 students of class XI at two public high schools in Palangka Raya City, the sample was taken using proportiona (PSQI ),te stratified random sampling. Adolescent sleep quality was measured using The Pittsburgh Sleep Quality Index questionnaire. Data were analyzed through Chi Square test. The results showed that female adolescent students were more dominant in having poor sleep quality as much as 59.2%. Adolescents' poor sleep quality due to an uncomfortable environment was 82.7% (p value 0.773), poor sleep quality in students who did not do physical exercise/not tired as much as 84.9% (p value 0.34). Students with light activities had poor sleep quality as much as 84.9% (p value 0.346). Students with light activity have poor sleep quality as much as 82.4% (p value 0.720). Students who have bad sleep habits before bedtime are 80.9% (p value 0.848). Factors that affect the quality of sleep for adolescents in the city of Palangka Raya are physical exercise and fatigue